One-lung ventilation for percutaneous thermal ablation of liver tumors in the hepatic dome. (1st January 2020) - Long, Yinglin; Zeng, Qingjing; He, Xuqi; Ye, Huolin; Su, Yating; Zheng, Rongqin; Yu, Jie; Xu, Erjiao; Li, Kai
Abstract: Purpose: To investigate the feasibility, efficacy and safety of one-lung ventilation for percutaneous thermal ablation of liver tumors in the hepatic dome. Materials and methods: From 5 January 2017 to 16 April 2019, 64 patients who underwent ultrasound-guided thermal ablation with a total of 75 liver malignant tumors located in the hepatic dome were enrolled in the present study. One-lung ventilation was employed to improve the acoustic window and protect the lung and diaphragm. If the one-lung ventilation was unsuccessful, artificial pleural effusion was added. The technical efficacy was confirmed by contrast-enhanced computed tomography/magnetic resonance imaging (CT/MRI) 1 month later. After that, CT/MRI was performed every 3–6 months. Results: Among the enrolled patients, the technical success rate of one lung ventilation was 92.2% (59/64). The visibility scores of tumors were improved significantly after one-lung ventilation compared to those before one-lung ventilation ( p < .001). Finally, 78.6% (55/70) of the tumors achieved clinical success of one-lung ventilation to become clearly visible and underwent thermal ablation. Fourteen of the remaining 15 tumors achieved a satisfactory acoustic window after combination of artificial pleural effusion. One lesion remained inconspicuous and partly affected by pulmonary gas. The follow-up period was 8 months (3–30 months). The technical efficacy rate was confirmed to be 100% (75/75). During the follow-up period, local tumor progression occurred in 2 patients (2/75, 2.7%). Major complications occurred in two patients (2/64, 3.1%) receiving one-lung ventilation. Conclusions: One-lung ventilation is a promising noninvasive method for the thermal ablation of hepatic dome tumors due to its efficacy and safety.